2018
DOI: 10.1021/acscatal.7b03205
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Dimerization and Oligomerization to 1-Butene and Higher Olefins with Chromium-Promoted Cobalt on Carbon Catalyst

Abstract: Industrial dimerization of ethylene to 1-butene is achieved with catalysts bearing ligand structures and activated by a co-catalyst. Here, we report that a Cr-promoted cobalt oxide on carbon catalyst was able to produce 1-butene with 53.5− 82.4% total selectivity at ethylene conversions between 8.9 and 31.5% without the use of a co-catalyst. The Cr-promoted catalyst showed enhanced activity and stability compared to the nonpromoted catalyst. The characterization results revealed that the incorporation of Cr in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Typically, this kind of fouling happens in several types of waste treatment systems. Lastly, fouling can be caused by a corrosion mechanism that is dependent on thermal resistance and surface roughness [29].…”
Section: A Fouling Problem In Alphabutol Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, this kind of fouling happens in several types of waste treatment systems. Lastly, fouling can be caused by a corrosion mechanism that is dependent on thermal resistance and surface roughness [29].…”
Section: A Fouling Problem In Alphabutol Processmentioning
confidence: 99%
“…Ibrahim et al [29] investigated the fouling mechanisms that occur in the heat exchangers of the naphtha hydrotreatment unit of the Horns oil refinery. Generally, fouling is caused by polymerization.…”
Section: A Fouling Problem In Alphabutol Processmentioning
confidence: 99%
“…Oligomerization reaction of ethylene has been studied on various heterogeneous catalysts such as, metal oxides and sulfates, micro and mesoporous aluminosilicates,, and metal organic frameworks (MOFs) . Compared to other solid catalysts for ethylene oligomerization reaction, nickel (Ni 2+ ) containing microporous materials (such as zeolites and MOFs) offer the opportunity to control and optimize reaction rate and selectivity of these reactions .…”
Section: Figurementioning
confidence: 99%
“…By calculating the activation energy, it was found that the concerted mechanism dominates the dimerization reaction. Namuangruk et al studied the dimerization of ethylene using the 84 T octahedral sieve model . In this model, the activation energy of the stepwise mechanism was much lower than the activation energy of the concerted one, indicating that the ethylene dimerization would proceed in the stepwise route.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this reaction also involves the processes of proton migration, CC bond formation, and deprotonation, which are the key steps in olefin cyclization, aromatization, and other reactions, such as methanol to olefin . Thus, in‐depth study of alkene dimerization has been done by both experimental and theoretical methods . Alkene dimerization generally proceeds with the help of catalysts.…”
Section: Introductionmentioning
confidence: 99%